Beyond Teeth: Insights into The Medical Health Status Of The Homeless And Urban Poor In Chow Kit - Ahmad Tarmidzi, Nor Azura; Hassan, Laila Azwa; Mohd Desa, Siti Nur Farhanah (International Journal of Human and Health Sciences (IJHHS), 2025)
Objectives: Homelessness is a longstanding issue in Malaysia, particularly in Kuala Lumpur, with an estimated 4,368 homeless individuals in 2019. Among these services, dental care is often also not excluded, leading to a myriad of medical problems among individuals who rely on communitybased dental services. A monthly dental community programme was initiated in 2017 by Dentistry for the Needy (DFTN) together with the Faculty of Dentistry, Universiti Sains Islam Malaysia (USIM). Other than prevention strategies, the aim of dental volunteerism is also to eliminate dental pain among the homeless and urban poor in Chow Kit, Kuala Lumpur. This study seeks to address this gap by assessing the status of medical problems among the homeless and urban poor attending Dental Community Service at Chow Kit, Kuala Lumpur. Methods: This retrospective study involved reviewing the dental records of patients attending the program in Chow Kit, Kuala Lumpur. Only complete dental records from July 2017 until March 2024 were included in this study. Data collected from the dental records includes the patient’s age, current medical status, blood pressure measurement, random blood glucose measurement and the dental treatment needed. Blood pressure measurement will only be done on adult patients and random blood glucose on patients 30 years and above. Results: The dental records of 170 patients were included in this study. The majority of the patients were Malaysians. Only 46 (27.1%) had reported existing medical illness(es) or condition(s), with 10 (21.7%) of them having more than one medical illness(es) or condition(s). However, a notable proportion exhibited concerning indicators, including random blood sugar levels exceeding 12 mmol/L and elevated blood pressure categorised as at risk, stage 1, stage 2 and stage 3. Conclusion: This study provides valuable insight to guide interventions to improve healthcare access and outcomes for this vulnerable population. International Journal of Human and Health Sciences Supplementary Issue 01: 2025 Page: S34